2010
DOI: 10.1111/j.1939-1676.2010.0609.x
|View full text |Cite
|
Sign up to set email alerts
|

Contrast-Enhanced Ultrasonography for Characterization of Focal Splenic Lesions in Dogs

Abstract: Background: Contrast-enhanced ultrasonography with perflubutane microbubbles improves the diagnostic accuracy to differentiate benign and malignant focal liver lesions in dogs.Hypothesis: Perflubutane microbubbles-enhanced ultrasonography is useful for differentiation of benign from malignant focal splenic lesions in dogs.Animals: Twenty-nine clinical dogs with single or multiple focal splenic lesions detected by conventional ultrasonography. Methods: Prospective clinical observational study. Perflubutane micr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
35
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(39 citation statements)
references
References 20 publications
2
35
2
Order By: Relevance
“…Splenic malignant neoplasms, most of which are hemangiosarcomas, frequently contain extensive hemorrhage or necrosis and so may be difficult to distinguish from hematoma on the basis of either gross or histologic examination . As noted above with respect to hepatic masses, other imaging techniques that depict vascularity of tissues also have limited potential to distinguish the histologic types of splenic mass …”
Section: Discussionmentioning
confidence: 99%
“…Splenic malignant neoplasms, most of which are hemangiosarcomas, frequently contain extensive hemorrhage or necrosis and so may be difficult to distinguish from hematoma on the basis of either gross or histologic examination . As noted above with respect to hepatic masses, other imaging techniques that depict vascularity of tissues also have limited potential to distinguish the histologic types of splenic mass …”
Section: Discussionmentioning
confidence: 99%
“…The obvious advantage of bolus injection is that it is easy to administer, less cumbersome, more repeatable [30], gives good tissue to tumor contrast and is the conventional method employed in characterizing nodular lesions [9, 12, 16, 20, 21, 27, 29]. However, contrast enhancement is too rapid and brief in the pancreas [6].…”
Section: Discussionmentioning
confidence: 99%
“…For bolus injection, we estimated that a microbubble contrast agent dose of 0.01 m l /kg would be suitable based on manufacturer’s recommendation (0.015 m l /kg) and clinical experiences with canine liver and spleen imaging in our facility [19,20,21]. For continuous infusion of microbubble contrast agent, based on preliminary studies (unpublished data), a dose 5 times of the bolus injection dose that was reported to be safe [17] was used.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The study population was recruited from canines with single or multiple focal splenic lesions detected by conventional ultrasonography in the Veterinary Teaching Hospital of the Graduate School of Veterinary Medicine, Hokkaido University [20]. Sonazoid (Daiichi-Sankyo, Tokyo, Japan) was used as the contrast agent.…”
Section: Experimental Datamentioning
confidence: 99%